Student Engagement Across Course Teaching Modalities - Carla VanBeselaere; Toni Roberts (Canadian Journal for the Scholarship of Teaching and Learning, 2024)
In this study, we compare student engagement across delivery modes (asynchronous online, synchronous online, and a mix of in-person, hyflex, and hybrid or blended teaching) at a small liberal arts undergraduate institution where faculty could choose their teaching mode. Student engagement involves students connecting with course material, the instructor, and fellow students. Student engagement is important due to its relationship with learning, retention, and student satisfaction. Using an online student survey and information on teaching modality, we examine how this mode affected students’ behavioural and affective engagement. Using both quantitative and qualitative analyses, investigate the following questions: how did the teaching mode affect student engagement and what can faculty do to encourage engagement? We find that student behaviours and beliefs reported in our survey indicate that the lack of in-person instruction did not significantly negatively affect student engagement at the university under study. We find that one of our measures of student engagement was higher in courses offered asynchronously online. Given this result, we use qualitative data analysis to untangle the factors that might support higher levels of engagement.